Capsule endoscopy in acute upper gastrointestinal hemorrhage: a prospective cohort study - Gralnek, I. M.; Ching, J. Y. L.; Maza, I.; Wu, J. C. Y.; Rainer, T. H.; Israelit, S.; Klein, A.; Chan, F. K. L.; Ephrath, H.; Eliakim, R.; Peled, R.; Sung, J. J. Y. (Endoscopy, 2013)
Background and study aims: Capsule endoscopy may play a role in the evaluation of patients presenting with acute upper gastrointestinal hemorrhage in the emergency department.Patients and methods: We evaluated adults with acute upper gastrointestinal hemorrhage presenting to the emergency departments of two academic centers. Patients ingested a wireless video capsule, which was followed immediately by a nasogastric tube aspiration and later by esophagogastroduodenoscopy (EGD). We compared capsule endoscopy with nasogastric tube aspiration for determination of the presence of blood, and with EGD for discrimination of the source of bleeding, identification of peptic/inflammatory lesions, safety, and patient satisfaction.Results: The study enrolled 49 patients (32 men, 17 women; mean age 58.3 ± 19 years), but three patients did not complete the capsule endoscopy and five were intolerant of the nasogastric tube. Blood was detected in the upper gastrointestinal tract significantly more often by capsule endoscopy (15 /18 [83.3 %]) than by nasogastric tube aspiration (6 /18 [33.3 %]; P = 0.035). There was no significant difference in the identification of peptic/inflammatory lesions between capsule endoscopy (27 /40 [67.5 %]) and EGD (35 /40 [87.5 %]; P = 0.10, OR 0.39 95 %CI 0.11 – 1.15). Capsule endoscopy reached the duodenum in 45 /46 patients (98 %). One patient (2.2 %) had self-limited shortness of breath and one (2.2 %) had coughing on capsule ingestion.Conclusions: In an emergency department setting, capsule endoscopy appears feasible and safe in people presenting with acute upper gastrointestinal hemorrhage. Capsule endoscopy identifies gross blood in the upper gastrointestinal tract, including the duodenum, significantly more often than nasogastric tube aspiration and identifies inflammatory lesions, as well as EGD. Capsule endoscopy may facilitate patient triage and earlier endoscopy, but should not be considered a substitute for EGD.